PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN PT. TIGA KHAYANGAN TIMUR (GSA PHILIPPINEAIRLINES INDONESIA) - Dea Shakina Guferol; Hariadi Hadisuwarno (LPPM Universitas Asa Indonesia, 2023)
This research aims to evaluate the impact of the work environment, leadership style, and compensation on employee loyalty PT. Tiga Khayangan Timur (GSA Philippine Airlines). Employee loyalty plays a crucial role in a company's success, as loyal employees tend to be more dedicated, productive, and positively contribute to the organization. The research sample consists of 30 respondents who are employees of PT. Tiga Khayangan Timur with a minimum of two years of work experience by applying saturated sample. Data was collected using questionnaires and analyzed using multiple linear regression analysis. The research findings indicate that the work environment, leadership style, and compensation have significant positive influence on employee loyalty at PT. Tiga Khayangan Timur (GSA Philippine Airlines) partially and simultaneously. Employees who work in a positive, inclusive, and supportive environment tend to be more loyal to the company. Furthermore, leadership style also has a positive and significant influence on employee loyalty. Effective leadership styles, such as transformative or democratic leadership, can establish an emotional bond between employees and the organization, thereby enhancing loyalty. Additionally, the research demonstrates that compensation has a positive and significant impact on employee loyalty. Employees who perceive their compensation as fair and adequate tend to exhibit higher levels of loyalty to the company. Relevant compensation components, such as competitive salaries, performance incentives, and additional benefits, can motivate employees to remain loyal to the organization. This research provides valuable insights for PT. Tiga Khayangan Timur (GSA Philippine Airlines) and other organizations in understanding the factors that contribute to employee loyalty. By focusing on and improving the work environment, leadership style, and compensation, companies can enhance employee loyalty, which, in turn, positively impacts performance and organizational sustainability.